Effects of Realaxation Therapy on Signs and Symptoms of Patients with TMD and Depression - A - Haghighat; M Nasiri; S Roshani; L Lottfi; N Kaviani (Isfahan University of Medical Sciences, 2005)
Introduction. Temporo-mandibular disorders (TMDs) are a group of chronic and common disease that a lot of skeletal, Dental and psychologic factors can have an effect on it. Proposed treatment to control this disorder consists of wide variety of drugs and non-drugs methods beside dental treatment. Some investigations have reffered to relation between TMDs and some psychologic factors such as depression. The aim of this study was to investigate affects of relaxation therapy on TMDs.Methods. This was a clinical trial study. The case group consisted of 25 patients with TMDs and an average mark of depression Beck index of 4/4. After Beck test, patients were taught relaxation therapy methods. These methods were done until-two weeks. After completion of methods, Beck test was done again and TMD patients were re-enaluated.Results. The average incidence of pain in TMJ (in function and Rest) the maximum opening, maximum protrusive and Lateral movement, deviation of mandible in maximum mouth opening, and Beck test mark before and after relaxation therapy were meaningful and changes showed decrease in TMDs signs.Discussion. Findings show the effect of psychologic factors as an independent etiologic factor or dependent precursor of TMDs. These effects shouldn't be ignored, therefore the relaxation therapy without any side effects can be a combined method with other methods to increase patients cooperation because of foovering the pain.Key words. Tempormandibular disorders, Depression, Relaxation therapy.